Simulation of Adaptive Control System for Multiagent Autonomous Underwater Cleaning Robots - Mohd Razali, Nurul Syafiqah; Isa, Khalid (Evolution in Electrical and Electronic Engineering, 2021)
Autonomous Underwater Vehicles (AUVs) have been extensively used in numerous applications and have gained worldwide recognition. These platforms can also be optimized and reconfigured according to the conditions in the aquatic world and should be autonomous. However, the AUVs may have problems in solving some tasks alone due to the large area of the underwater environment, and the underwater environment also had led to many problems in the kind of its cleanliness, which mostly caused by the bio-fouling activity problem. Using such a method may affect the system's stability and reliability. Therefore, this project is purposely to design an adaptive control system for multiagent autonomous underwater cleaning robots that can be applied to solve the problems of the underwater environment cleanliness, single robot problems, and avoid insignificant techniques that may cause faulty to the system. The MATLAB and Simulink software has been used in this project to design the adaptive control system of the multiagent autonomous underwater cleaning robots and simulate the designed controllers with multiple uncertain parameters together with a disturbance to be analyzed. The collected result consists of the designed 3D model using SolidWorks, a mathematical modelling structure of the robot, the analysis of open-loop control system, closed-loop control system of LQR, and the adaptive controller of MPC and lastly, the design of the multiagent system model structure for this work. The results show the adaptiveness, adjustment, and stability for the adaptive control system of multiagent underwater cleaning robots in order to cope with the situations of the underwater environment by using simulation.